2018
DOI: 10.1589/jpts.30.82
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pelvic tilt angles and forced vital capacity in healthy individuals

Abstract: [Purpose] The purpose of this study was to investigate the effect of pelvic tilt angles and lung function in participants performing pelvic tilts on a ball. [Subjects and Methods] Eighteen subjects participated in this study. While they performed pelvic tilt on sitting at a ball, the peak expiratory flow (PEF) and forced expiratory volume in one second (FEV1) were measured at 10 degrees of anterior and posterior pelvic tilt, respectively, and neutral position. The repeated measure ANOVA was performed, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The results showed that FVC, FEV1.0 and PFR were significantly lower at 30° PPTS than those at 0° PPTS. Previous studies have reported that PPTS leads to decreased respiratory function 13,14) . Takeda et al 20) reported a statistically significant decrease in FVC at 30° PPTS compared to the control group, which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results showed that FVC, FEV1.0 and PFR were significantly lower at 30° PPTS than those at 0° PPTS. Previous studies have reported that PPTS leads to decreased respiratory function 13,14) . Takeda et al 20) reported a statistically significant decrease in FVC at 30° PPTS compared to the control group, which is consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, PPTS is suggested to be strongly associated with certain respiratory function. Hwang and Kim 13) and Lin et al 14) showed that forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1.0), and peak flow rate (PFR) were lower in the PPTS. FVC, FEV1.0, and PFR are used for diagnosis of lung function and respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%